Sand casting coating capable of preventing generation of gray cast iron nitrogen holes and preparation method of sand casting coating
By adding specific components to the casting coating and using ultrasonic technology to make it densely dispersed, the problem of nitrogen pore formation in the casting is solved, the stability and air resistance of the casting are improved, the operation is simplified and the cost is reduced.
Patent Information
- Application Number
- CN202411311296.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-09-20
AI Technical Summary
During the casting process, the solubility of nitrogen in the iron liquid decreases, resulting in the formation of nitrogen pores and affecting the stability of the casting.
A sand casting coating including basalt fibers, zirconia microspheres, alumina powder and rare earth element powder is used to disperse it densely through ultrasonic technology to form a high-temperature stable and dense protective film to prevent gas from penetrating into the iron liquid.
It effectively reduces the formation of nitrogen pores, improves the high-temperature stability, strength, toughness and density of castings, enhances the anti-gas effect, simplifies the operation process and reduces production costs.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of casting coatings, and in particular to a sand casting coating for preventing nitrogen pores from being generated in grey cast iron and a preparation method thereof. Background Art
[0002] Currently, there are two main sources of nitrogen in molten iron. One is the nitrogen contained in the molten metal itself before casting; the other is that the nitrogen-containing resin decomposes into NH2 when heated, and NH2 dissociates on the surface of the molten metal, NH2-[N]+3 / 2H2. A considerable part of the [N] atoms enters the metal surface layer of the casting metal section which is still in a molten state, and diffuses from the surface to the inside.
[0003] Nitrogen pores are common defects in the production of gray iron castings. The main reason for their occurrence is that the solubility of nitrogen in the molten iron during the solidification process shows an overall downward trend. When the nitrogen content in the molten iron exceeds its maximum solubility, it will precipitate in the form of nitrogen, thereby forming pores in the casting, which has a certain impact on the material of the casting and reduces the stability of the casting in later use.
[0004] To this end, the present invention is proposed. Summary of the invention
[0005] The main purpose of the present invention is to provide a sand casting coating for preventing nitrogen pores from forming in gray cast iron and a preparation method thereof. The sand casting coating in the present invention has strong high-temperature stability, strength, toughness and density, can form a dense protective film on the surface of the sand mold, and effectively prevent the gas in the sand mold from penetrating into the molten iron.
[0006] In order to achieve the above objectives, the present invention provides the following technical solutions.
[0007] A first aspect of the present invention provides a sand casting coating for preventing nitrogen pores in grey cast iron, which comprises a base material and an additive, wherein the additive comprises the following components in percentage by mass:
[0008] Basalt fiber 15% to 35%, zirconium oxide microspheres 1% to 10%, aluminum oxide powder 40% to 50%, rare earth element powder 0.5% to 1.5%.
[0009] Basalt fiber is a new type of inorganic fiber with good heat resistance and toughness. Basalt fiber can maintain its performance in high temperature environment and is not easy to deform or decompose, so it can improve the high temperature stability of the coating. Adding basalt fiber to the coating can also increase the strength and toughness of the coating and improve its tensile and impact resistance.
[0010] Adding zirconium oxide microspheres to the coating can, on the one hand, be used in conjunction with basalt fibers. After the reaction of the high-temperature production process, the microspheres are more densely dispersed, making the overall coating more dense and complete, reducing the risk of gas intrusion and improving the protective effect. On the other hand, zirconium oxide can promote the conversion of nitrogen. Even if NH2 decomposes to produce nitrogen, the gas produced under such catalytic conditions is usually insoluble in molten iron and does not form subcutaneous pores.
[0011] Alumina can improve the fluidity of the coating, making it easier to apply and evenly cover the surface of the casting, and improve the flatness and density of the coating. In addition, the microporous structure of alumina can help gas escape from the coating more easily and reduce the formation of nitrogen pores.
[0012] In an embodiment of the present invention, the rare earth element powder includes one of cerium oxide powder and lanthanum oxide powder.
[0013] In an embodiment of the present invention, the mass ratio of the additive to the base material is (2-3):10.
[0014] In an embodiment of the present invention, the base material comprises the following components in percentage by mass: 30-50% filler, 1%-8% binder, 2%-10% suspending agent, 0.5%-1.5% thickener, and the balance is solvent.
[0015] In an embodiment of the present invention, the filler includes one or more of alumina and silica.
[0016] In an embodiment of the present invention, the mass ratio of the aluminum oxide to the silicon dioxide is (2-3):(1-2).
[0017] In an embodiment of the present invention, the binder includes at least one of phenolic resin, furan resin, isocyanate, and urethane resin.
[0018] In an embodiment of the present invention, the suspending agent includes at least one of organic bentonite, sodium carboxymethyl cellulose, and polyvinyl butyral.
[0019] In an embodiment of the present invention, the thickener includes at least one of ethyl cellulose and propyl cellulose.
[0020] In an embodiment of the present invention, the solvent includes at least one of ethanol and isopropanol.
[0021] The second aspect of the present invention provides a method for preparing the sand casting coating according to the first aspect of the present invention, which comprises the following steps: preparing a base material; preparing an additive: mixing basalt fiber, zirconium oxide microspheres, aluminum oxide powder and rare earth element powder and grinding them to obtain the additive; the particle size of the additive is 10 μm to 15 μm; under stirring conditions, mechanically mixing and ultrasonically mixing the base material and the additive in sequence to obtain the sand casting coating.
[0022] In an embodiment of the present invention, basalt fiber, zirconium oxide microspheres, aluminum oxide powder and rare earth element powder are mixed in a mixer for 30 to 90 minutes, and ground in a three-roll grinder at a grinding frequency of 100 to 200 r / min and a grinding time of 10 to 30 minutes to ensure that the particle size of the additive is 10 μm to 15 μm.
[0023] In an embodiment of the present invention, the preparation of the base material comprises the following steps: mixing the filler with the binder, the suspending agent, the thickener and the solvent and stirring them uniformly to obtain the base material.
[0024] In an embodiment of the present invention, the stirring speed of the mechanical mixing of the base material and the additive is 300 r / min to 700 r / min, and the stirring time is 10 min to 30 min.
[0025] In an embodiment of the present invention, the ultrasonic temperature of the ultrasonic mixing is 5° C. to 15° C., the ultrasonic frequency is 20 kHz to 30 kHz, and the ultrasonic time is 0.5 h to 3 h.
[0026] Under the ultrasonic process of the present invention, the coating is more densely dispersed, making the overall coating denser and more complete, reducing the risk of gas intrusion, and improving the protective effect. It has strong high-temperature stability, strength, toughness and density, and can form a dense protective film on the surface of the sand mold to effectively prevent the gas in the sand mold from penetrating into the molten iron.
[0027] Compared with the prior art, the present invention achieves the following technical effects:
[0028] 1. The sand casting coating of the present invention increases the strength and toughness of the coating by adding basalt fiber material, thereby improving its tensile and impact resistance.
[0029] 2. The zirconium oxide microspheres and rare earth powder added to the sand casting coating of the present invention can also promote the thermal decomposition of the nitrogen-containing resin. The gas generated under such catalytic conditions is usually insoluble in molten iron and does not form subcutaneous pores.
[0030] 3. The aluminum oxide in the sand casting coating of the present invention can improve the fluidity of the coating, make the coating easier to apply and evenly cover the casting surface, and improve the flatness and density of the coating. In addition, the microporous structure of aluminum oxide can help gas escape from the coating more easily and reduce the formation of nitrogen pores.
[0031] 4. The basalt fiber, zirconium oxide microspheres and rare earth element powder in the sand casting coating of the present invention are used in combination. Under the action of the ultrasonic process, they are more densely dispersed, making the coating as a whole more dense and complete, reducing the risk of gas intrusion, and improving the protective effect. It has strong high-temperature stability, strength, toughness and density, and can form a dense protective film on the surface of the sand mold, effectively preventing the gas in the sand mold from penetrating into the molten iron.
[0032] 5. The preparation method of the present invention does not require any additional steps or special equipment, and has strong applicability.
[0033] 6. The preparation method of the present invention has low production cost and unchanged production efficiency.
[0034] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention, it can be implemented according to the contents of the specification. In order to make the above and other purposes, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are listed below. DETAILED DESCRIPTION
[0035] Embodiments of the present invention are described below. However, it should be understood that these descriptions are exemplary only and are not intended to limit the scope of the present invention. In addition, in the following description, descriptions of well-known structures and technologies are omitted to avoid unnecessary confusion of the concept of the present invention.
[0036] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which the present invention belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention; the terms "including" and "having" in the description and claims of the present invention and any variations thereof are intended to cover non-exclusive inclusions.
[0037] In the description of the embodiments of the present invention, technical terms such as "first" and "second" are only used to distinguish different objects and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features.
[0038] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present invention. The appearance of the phrase in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0039] In the description of the embodiments of the present invention, the term "and / or" is only a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B may represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0040] In the description of the embodiments of the present invention, the term "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple pieces" refers to more than two pieces (including two pieces).
[0041] In the description of the embodiments of the present invention, unless otherwise clearly specified and limited, technical terms such as "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements. For ordinary technicians in this field, the specific meanings of the above terms in the embodiments of the present invention can be understood according to specific circumstances.
[0042] In view of the fact that the current means of avoiding the generation of nitrogen pore defects is mainly to reduce the gas emission of the core and promote the discharge of gas in the core to produce a gas-proof effect. For example, the prior art discloses a resin with low gas emission and a preparation method thereof, in which formaldehyde and urea are not used in the synthesis of furan resin, and no formaldehyde gas and nitrogen oxides are released during use, which is beneficial to the environment and reduces the gas emission of the resin; ethyl silicate and polytetrahydrofuran are used to further seal the hydroxyl groups of low molecular weight furfuryl alcohol, so that the volatility of furfuryl alcohol in the resin is reduced, and finally the free furfuryl alcohol accounts for only one tenth of the total amount of furfuryl alcohol, which effectively reduces the volatilization of the resin and the gas emission during pouring. Another example is a method for manufacturing a low-gassing casting core disclosed in the prior art. The silica sand used to make the core is baked at 580-600°C, and the silica sand is taken out after it turns red; the core is made hollow by pre-buried pipelines or exhaust ropes; after the core is made, the core is placed in a vacuum device to remove the gas in the core; a layer of casting coating is evenly applied on the surface of the core; after the coating is naturally dried, the mold surface coating is grinded with sandpaper until it is uniform and smooth, and there is no accumulation on the surface of the mold; a layer of carbon black is evenly smoked on the surface of the mold with a burning acetylene nozzle. Taking the above measures, the coating and carbon black layer will produce a strong reducing atmosphere when the molten metal is poured, and an air film and a carbon film will be formed at the interface between the casting and the coating, which prevents the interaction between the molten metal and the sand mold and produces an anti-gas effect. However, the above two technical means have the disadvantages of complicated operation process, the need to configure special equipment, increased production cost, and reduced production efficiency.
[0043] Of course, there are also schemes in the prior art to improve the sand casting coating, such as adding iron oxide and active high-temperature oxidation flux, thereby using highly active zirconium silicate and high-temperature oxidant materials, so that the coating melts under heat at high temperature to form a dense shielding coating, reducing the penetration of gas into the molten metal, and using active coating to increase the sintering ability of the coating at high temperature, forming a liquid coating film, effectively shielding the gas from entering the molten metal, and improving the stability of the casting in later use. However, although this technical solution increases the sintering ability of the coating at high temperature to a certain extent, the liquid coating film formed has poor density and poor gas shielding.
[0044] To this end, the present invention provides a casting sand mold coating for preventing nitrogen pores in gray cast iron. By commingling the base material and the additive under the action of an ultrasonic process, the high-temperature stability, strength, toughness and density of the coating as a whole are improved, and the interaction between the molten metal and the sand mold is prevented, thereby producing an anti-gas effect. In addition, the coating can also promote the thermal decomposition of nitrogen-containing resins. The gas produced under such catalytic conditions is usually also insoluble in the molten iron and does not form subcutaneous pores. Moreover, the coating does not need to be equipped with special production equipment during use, is easy to operate, and is easy to apply to production sites.
[0045] The first aspect of the present invention provides a sand casting coating for preventing nitrogen pores in grey cast iron, which comprises a base material and an additive, wherein the additive comprises the following components in percentage by mass:
[0046] Basalt fiber 15% to 35%, zirconium oxide microspheres 1% to 10%, aluminum oxide powder 40% to 50%, rare earth element powder 0.5% to 1.5%.
[0047] In an embodiment of the present invention, the mass percentage of basalt fiber in the additive can be one of 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35% or any value satisfying the above range.
[0048] In an embodiment of the present invention, the mass percentage of zirconium oxide microspheres in the additive can be one of 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% or any value satisfying the above range.
[0049] In an embodiment of the present invention, the mass percentage of alumina powder in the additive may be one of 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50% or any value satisfying the above range.
[0050] In an embodiment of the present invention, the mass percentage of rare earth element powder in the additive can be one of 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5% or any value that meets the above range.
[0051] In the embodiment of the present invention, the rare earth element powder can be cerium oxide powder. Of course, other rare earth element powders, such as lanthanum oxide powder, can also be selected according to the situation.
[0052] In an embodiment of the present invention, the mass ratio of the additive to the base material may be (2-3):10. For example, the mass ratio of the additive to the base material may be 2:10, 3:10 or any value satisfying the above range.
[0053] In an embodiment of the present invention, the base material includes the following components in mass percentage:
[0054] Filler 30-50%, binder 1%-8%, suspending agent 2%-10%, thickener 0.5%-1.5%, and the balance is solvent.
[0055] In the embodiment of the present invention, the sand casting coating is composed of base materials such as fillers, binders, suspending agents, thickeners, solvents, and additives such as basalt fibers, zirconium oxide microspheres, aluminum oxide powders, and rare earth element powders.
[0056] In an embodiment of the present invention, the mass percentage of the filler in the base material can be one of 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50% or any value that meets the above range.
[0057] In an embodiment of the present invention, the filler includes one or more of aluminum oxide and silicon dioxide, for example, the filler consists of aluminum oxide and silicon dioxide.
[0058] In an embodiment of the present invention, the mass ratio of aluminum oxide to silicon dioxide is (2-3):(1-2). For example, the mass ratio of aluminum oxide to silicon dioxide can be one of 2:1, 2:2, 3:1, 3:2 or any value satisfying the above range.
[0059] In an embodiment of the present invention, the mass percentage of the binder in the base material may be one of 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8% or any value satisfying the above range.
[0060] In the embodiment of the present invention, the binder may be phenolic resin. Of course, other materials such as furan resin, isocyanate, urethane resin, etc. may be selected as the binder in the embodiment of the present invention according to the situation.
[0061] In an embodiment of the present invention, the mass percentage of the suspending agent in the base material can be one of 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% or any value satisfying the above range.
[0062] In the embodiment of the present invention, the suspending agent can be organic bentonite. Of course, other materials such as sodium carboxymethyl cellulose, polyvinyl butyral, etc. can also be selected as the suspending agent in the embodiment of the present invention according to the situation.
[0063] In an embodiment of the present invention, the mass percentage of the thickener in the base material can be one of 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5% or any value that meets the above range.
[0064] In the embodiment of the present invention, the thickener may be an ethyl cellulose solution. Of course, other solutions, such as propyl cellulose, etc., may also be selected as the thickener in the embodiment of the present invention according to the situation.
[0065] In an embodiment of the present invention, the solvent may be ethanol. Of course, other solvents such as isopropanol may also be selected according to circumstances.
[0066] The second aspect of the present invention provides a method for preparing the sand casting coating for preventing nitrogen pores in grey cast iron according to the first aspect of the present invention, which is specifically carried out according to the following steps.
[0067] (1) Prepare base material.
[0068] The filler is mixed with a binder, a suspending agent, a thickener and a solvent and stirred evenly to obtain a base material.
[0069] In an embodiment of the present invention, powdered alumina and silica are added to a mixer and mixed for 30 to 90 minutes; then phenolic resin, organic bentonite, ethyl cellulose and ethanol are added to the obtained mixed filler, mixed for 30 to 90 minutes, and then introduced into a high-speed disperser with a disperser frequency of 100 to 200 r / min and a stirring time of 10 to 30 minutes until uniform.
[0070] In an embodiment of the present invention, the mixing or grinding time can be one of 30min, 40min, 50min, 60min, 70min, 80min, 90min or any value satisfying the above range. The frequency of the disperser can be one of 100r / min, 110r / min, 120r / min, 130r / min, 140r / min, 150r / min, 160r / min, 170r / min, 180r / min, 190r / min, 200r / min or any value satisfying the above range, and the dispersion time can be one of 10min, 15min, 20min, 25min, 30min or any value satisfying the above range.
[0071] (2) Prepare additives.
[0072] The basalt fiber, zirconium oxide microspheres, aluminum oxide and rare earth element powder are mixed and ground to obtain an additive.
[0073] In an embodiment of the present invention, basalt fiber, zirconium oxide microspheres, aluminum oxide and rare earth element powder are added to a mixer and mixed for a period of time, such as 30 minutes to 90 minutes, and then ground in a three-roller grinder for a period of time, such as 10 minutes to 30 minutes.
[0074] In an embodiment of the present invention, the grinding frequency of the grinder can be 100 r / min to 200 r / min, for example, the grinding frequency can be one of 100 r / min, 110 r / min, 120 r / min, 130 r / min, 140 r / min, 150 r / min, 160 r / min, 170 r / min, 180 r / min, 190 r / min, 200 r / min or any value satisfying the above range value. The grinding time can be one of 10 min, 15 min, 20 min, 25 min, 30 min or any value satisfying the above range value. The mixing time in the mixer can be one of 30 min, 40 min, 50 min, 60 min, 70 min, 80 min, 90 min or any value satisfying the above range value.
[0075] (3) Under stirring conditions, the base material and the additive are mechanically mixed and ultrasonically mixed in sequence to obtain a sand casting coating.
[0076] In an embodiment of the present invention, the base material and the additive are introduced into a high-speed mixer according to a required ratio, and after being uniformly stirred, they are placed in an ultrasonic processor, and the ultrasonic processor is started to perform ultrasonic mixing.
[0077] In an embodiment of the present invention, the stirring speed of mechanical mixing in the high-speed stirrer is 300r / min to 700r / min, and the stirring time is 10min to 30min. For example, the stirring speed can be one of 300r / min, 350r / min, 400r / min, 450r / min, 500r / min, 550r / min, 600r / min, 650r / min, 700r / min or any value satisfying the above range value. The stirring time can be one of 10min, 10min, 15min, 20min, 25min, 30min or any value satisfying the above range value.
[0078] In an embodiment of the present invention, the ultrasonic temperature of ultrasonic mixing can be one of 5°C, 6°C, 7°C, 8°C, 9°C, 10°C, 11°C, 12°C, 13°C, 14°C, 15°C or any value satisfying the above range. The ultrasonic frequency can be one of 20kHz, 21kHz, 22kHz, 23kHz, 24kHz, 25kHz, 26kHz, 27kHz, 28kHz, 29kHz, 30kHz or any value satisfying the above range. The ultrasonic time can be one of 0.5h, 1h, 1.5h, 2h, 2.5h, 3h or any value satisfying the above range.
[0079] In the embodiment of the present invention, under the action of ultrasound, the density between particles is higher, which is a key technology to enhance the density of the coating material. In addition, the high thermal conductivity of the basalt fiber material itself can quickly evaporate the flux in the coating to reduce the generation of fine lines and voids, thereby obtaining a sand casting coating that prevents the generation of nitrogen pores in gray cast iron.
[0080] The sand casting coating for preventing nitrogen pores from forming in grey cast iron and the preparation method thereof in the present invention will be described in detail below in conjunction with specific embodiments.
[0081] If no specific technology or conditions are specified in the examples, the technology or conditions described in the literature in this field or the product instructions are used. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased through regular channels. The experimental methods in the following examples are all conventional methods unless otherwise specified. The test materials used in the following examples are all commercially available products unless otherwise specified.
[0082] Example 1
[0083] S1: Add 20% aluminum oxide and 20% silicon oxide in powder form into a mixer and mix for 30 minutes; add 1% phenolic resin, 10% organic bentonite, 1.5% ethyl cellulose and ethanol into the mixed base material, mix and introduce into a high-speed disperser for uniform stirring at a frequency of 150r / min.
[0084] S2: Add 15% of basalt fiber, 10% of zirconium oxide microspheres, 50% of aluminum oxide powder and 1.5% of cerium oxide powder into a mixer and mix for 30 minutes, then grind with a three-roll grinder for 1 hour and set aside.
[0085] S3: 100% base material and 20% additive are introduced into a high-speed mixer and stirred at a speed of 300 r / min. After stirring evenly, the mixture is placed in an ultrasonic processor, the ultrasonic processor is started, and ultrasonic mixing is started. The ultrasonic mixing temperature is 10° C., the frequency is 25 kHz, and the time is 2 hours to obtain a sand casting coating that prevents nitrogen pores in gray cast iron.
[0086] Example 2
[0087] S1: Add 30% aluminum oxide and 10% silicon oxide in powder form into a mixer and mix for 60 minutes; add 8% phenolic resin, 2% organic bentonite, 0.5% ethyl cellulose and ethanol into the mixed base material, mix and introduce into a high-speed disperser for uniform stirring at a frequency of 200 r / min for 10 minutes.
[0088] S2: Add 35% of basalt fiber, 1% of zirconium oxide microspheres, 40% of aluminum oxide powder and 0.5% of cerium oxide powder into a mixer and mix for 30 minutes, then grind with a three-roll grinder for 1 hour and set aside.
[0089] S3: 100% base material and 30% additive are introduced into a high-speed mixer and stirred at a speed of 600 r / min for 20 min. After stirring evenly, the mixture is placed in an ultrasonic processor, the ultrasonic processor is started, and ultrasonic mixing is started at a temperature of 15° C., a frequency of 20 kHz, and a time of 1 h to obtain a sand casting coating that prevents nitrogen pores in gray cast iron.
[0090] Example 3
[0091] S1: Add 25% of powdered aluminum oxide and 15% of silicon oxide into a mixer and mix for 90 minutes; add 5% of phenolic resin, 6% of organic bentonite, 1.0% of ethyl cellulose and ethanol into the mixed base material, mix and introduce into a high-speed disperser for uniform stirring at a frequency of 150 r / min for 10 minutes.
[0092] S2: Add 25% of basalt fiber, 6% of zirconium oxide microspheres, 45% of aluminum oxide powder and 1.0% of cerium oxide powder into a mixer and mix for 30 minutes, then grind with a three-roll grinder for 1 hour and set aside.
[0093] S3: 100% base material and 30% additive are introduced into a high-speed mixer for stirring. After stirring evenly, the mixture is placed in an ultrasonic processor, and the ultrasonic processor is started to start ultrasonic mixing. The ultrasonic mixing temperature is 5° C., the frequency is 30 kHz, and the time is 3 hours to obtain a sand casting coating for preventing nitrogen pores in gray cast iron.
[0094] In the present invention, the base material and the additive are melted together under the action of ultrasonic technology, thereby improving the high-temperature stability, strength, toughness and density of the entire coating, preventing the interaction between the molten metal and the sand mold, and producing an anti-gas effect.
[0095] In addition, the coating can also promote the thermal decomposition of nitrogen-containing resins. The gas produced under such catalytic conditions is usually insoluble in molten iron and forms subcutaneous pores, which effectively shield the gas from entering the molten metal, improve the material quality of the casting, and thus improve the stability of the casting in later use.
[0096] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them; although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention, and they should all be included in the scope of the claims and specification of the present invention. In particular, as long as there is no structural conflict, the various technical features mentioned in each embodiment can be combined in any way. The present invention is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.
Claims
1. A sand casting coating for preventing nitrogen pores from forming in grey cast iron, characterized in that: It comprises a base material and an additive, wherein the additive comprises the following components in percentage by mass: Basalt fiber 15% to 35%, zirconium oxide microspheres 1% to 10%, aluminum oxide powder 40% to 50%, rare earth element powder 0.5% to 1.5%.
2. The sand casting coating according to claim 1, characterized in that: The rare earth element powder includes one of cerium oxide powder and lanthanum oxide powder; Preferably, the mass ratio of the additive to the base material is (2-3):
10.
3. The sand casting coating according to claim 1, characterized in that: The base material comprises the following components in percentage by mass: The filler is 30% to 50%, the binder is 1% to 8%, the suspending agent is 2% to 10%, the thickener is 0.5% to 1.5%, and the balance is the solvent.
4. The sand casting coating according to claim 3, characterized in that: The filler includes one or more of alumina and silica; Preferably, the mass ratio of the aluminum oxide to the silicon dioxide is (2-3):(1-2).
5. The sand casting coating according to claim 3, characterized in that: The binder includes at least one of phenolic resin, furan resin, isocyanate, and urethane resin; Preferably, the suspending agent includes at least one of organic bentonite, sodium carboxymethyl cellulose and polyvinyl butyral.
6. The sand casting coating according to claim 3, characterized in that: The thickener includes at least one of ethyl cellulose and propyl cellulose; Preferably, the solvent includes at least one of ethanol and isopropanol.
7. A method for preparing a sand casting coating according to any one of claims 1 to 6, characterized in that: The preparation method comprises the following steps: preparing a base material; Preparation of additives: mixing basalt fiber, zirconium oxide microspheres, aluminum oxide powder and rare earth element powder and grinding them to obtain the additive; the particle size of the additive is 10 μm to 15 μm; Under stirring conditions, the base material and the additive are mechanically mixed and ultrasonically mixed in sequence to obtain the sand casting coating.
8. The preparation method according to claim 7, characterized in that: The basalt fiber, zirconium oxide microspheres, aluminum oxide powder and rare earth element powder are mixed in a mixer for 30 to 90 minutes, and ground in a three-roller grinder at a grinding frequency of 100 to 200 r / min and a grinding time of 10 to 30 minutes.
9. The preparation method according to claim 8, characterized in that: The preparation of the base material comprises the following steps: The filler is mixed with a binder, a suspending agent, a thickener and a solvent and stirred evenly to obtain the base material.
10. The preparation method according to claim 8, characterized in that: The stirring speed of the mechanical mixing of the base material and the additive is 300r / min to 700r / min, and the stirring time is 10min to 30min; Preferably, the ultrasonic mixing has an ultrasonic temperature of 5° C. to 15° C., an ultrasonic frequency of 20 kHz to 30 kHz, and an ultrasonic time of 0.5 h to 3 h.
Citation Information
Patent Citations
Method for eliminating subsurface pores of nodular iron casting
CN101823125A
Fire resistant material and preparation method thereof
CN105130474A
High-strength isopropanol-based coating for lost foam casting and preparing method of coating
CN106141079A
Preparation method of slurry for aluminum alloy investment casting shell
CN110640083A
Inorganic matrix composition and composites incorporating the matrix composition
US20020058576A1